COMPARATIVE ECONOMIC ANALYSIS OF EARTHEN POND AND CONCRETE TANK PRODUCTION SYSTEMS AMONG FISH FARMERS IN LAGOS STATE, NIGERIA - OLAOYE, O. J.; OJEBIYI, W. G.; OYETADE, O. P.; AJIBOYE, K. J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study compared the economic analysis of earthen pond and concrete tank production systems among fish farmers in Ikorodu Local Government Area, Lagos State, Nigeria, using a cross-sectional survey research design. A two-stage sampling procedure was adopted in selecting 120 fish farmers from Ikorodu Fish Farm Estate in Lagos State. Data were collected using an interview guide and analyzed using frequency, mean, standard deviation, budgetary technique and student-t test. Results revealed that most earthen pond fish farmers - EPFF (86.0%) and concrete tank fish farmers - CTFF (87.0%) were males. Cost-return analyses revealed that EPFF earned an average of N8,611,046.50 while CTFF earned an average of N6,387,896.10 as total revenue with gross margins of N4,229,751.10 and N1,956,991.10 for EPFF and CTFF, respectively. Also, feed costs accounted for 88.6% and 88.9% of total production costs using earthen ponds and concrete tanks, respectively. The net fish farming profits were N3,993,479.07 and N1,697,639.7 for EPFF and CTFF, respectively, while the benefit-cost ratios were 1.86 and 1.36, respectively. High cost of feed, transportation and inadequate capital were the most severe constraints in both production systems. Significant differences were established in the number of ponds (t=5.71, p≤0.01), stocking density (t=6.36, p≤0.01), net fish farming income (t=3.972, p≤0.01) and gross margin (t=3.827, p≤0.01) of the earthen pond and concrete tank fish farmers. The study concluded that the earthen pond culture system was economically better than the concrete tank culture. It was recommended that new entrants into fish farming should utilize the earthen ponds.